The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
MAR 2022
DOI: 10.24191/mar.v21i02-01
|View full text |Cite
|
Sign up to set email alerts
|

Financial Management Practices in Malaysian Islamic Social Enterprise (ISE)

Abstract: This study examined the role of financial management practices consisting of financial disclosure, internal control, financial planning and budgeting and financial performance management in Islamic Social Enterprises (ISEs) in Malaysia. A survey method was used and 102 financial officers in Malaysian ISEs had responded. T-test analysis was used to examine the significant differences based on Malaysian ISEs attributes including years of operation, organisational size and income generation level. This study foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Based on the recent study on financial management in ISE, it is found that financial management, Islamic work ethic and financial governance significantly affect ISE's accountability (Kamaruddin et al, 2021). Similarly, another study related by Kamaruddin et al (2022) discovers current financial management components' practices in Malaysian ISEs. However, both findings are quite general, and no detailed study has been made to investigate these financial management practices and its impact with accountability.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the recent study on financial management in ISE, it is found that financial management, Islamic work ethic and financial governance significantly affect ISE's accountability (Kamaruddin et al, 2021). Similarly, another study related by Kamaruddin et al (2022) discovers current financial management components' practices in Malaysian ISEs. However, both findings are quite general, and no detailed study has been made to investigate these financial management practices and its impact with accountability.…”
Section: Introductionmentioning
confidence: 98%